The Influence of Field Agricultural Extension (PPL) Development on The Dynamics of Farmer Groups - Yayat Rahmat Hidayat; Achmad Faqih; Toni Hidayat; Sunaenah Sunaenah; Akhmad Faizal; Heru Hermawan (Pusat Publikasi Nusantara, 2023)
The role of agricultural extension workers is needed to improve the abilities, knowledge and skills of each member of the farmer group so that the goals of the farmer group can be achieved properly. An extension worker in fostering farmer groups in an effort to increase production and productivity by helping to develop definitive group plans (RDK) and (RDKK). In addition, in terms of fostering farmer groups, extension workers implement the Training and Visit (LAKU) work system. The purpose of this study is to determine the influence of agricultural extension workers in assisting the preparation of DRC and RDKK; knowing the development of agricultural extension workers in the Training and Visit Work System (LAKU); knowing the influence of agricultural extension worker development in assisting the preparation of RDK RDKK and agricultural extension worker development in the Training and Visit Work System (LAKU) on the Dynamics of Farmer Groups in the Farmer Fortune Association, Sukagumiwang Village, Sukagumiwang District, Indramayu Regency. This research was conducted in Sukagumiwang Village, Sukagumiwang District, Indramayu Regency. The research was carried out in October-December 2022. The respondents in this study were Farmer Groups in the Farmer Fortune Association (GAPOKTAN) as many as 89 people. The design used in this study was quantitative descriptive. Data analysis techniques in this study use descriptive analysis and multiple linear regression analysis, f-Test, t-Test and coefficient of determination. The results showed that the development of agricultural extension workers in assisting the preparation of RDK RDKK and the training and visit work system (LAKU) had a real effect on the Dynamics of Farmer Groups in the Farmer Fortune Association. The development of agricultural extension workers in assisting the preparation of RDK RDKK with the development of agricultural extension workers in the Training and Visit Work System has a real effect together on the Dynamics of Farmer Groups in the Farmer Fortune Association.